Effect of LiCoO2 on the positive temperature coefficient effect (PTC) properties of semiconductive composites and its ability to inhibit space charge injection. (24th January 2022) - Wang, Ciyao; Chen, Shumei; Long, Yu; Liu, Yujia; Hao, Chuncheng; Lei, Qingquan
Abstract: The semiconductive shield layer is between the conductive core and the insulation layer of high voltage direct current transmission cables and plays an important role in suppressing the accumulation of space charge in the insulation layer. Since the prevalent positive temperature coefficient effect (PTC) of the semiconducting layer leads to cable ageing and failure, this paper proposes the use of lithium cobaltate to modify the semiconducting shield to suppress its PTC effect and improve its ability to inhibit space charge injection. The ionic conductor LiCoO2 was prepared by the sol–gel method. LiCoO2 particles with particle sizes ranging from tens to hundreds of nanometres were obtained by ball milling. The prepared LiCoO2 was used as a filler to modify the carbon black (CB)/ethylene vinyl acetate copolymer (EVA)/low density polyethylene (LDPE) composites. After melt blending and moulding cross‐linking, LiCoO2 /CB/EVA/LDPE semiconductive shielding specimens were successfully fabricated. Resistivity, Thermally Stimulated Depolarisation Currents (TSDC), and pulsed electro‐acoustic measurements were conducted for the prepared specimens. The PTC effect, which is common in polymer composites, was successfully suppressed, and the PTC strength was reduced by 17%. The resistivity of the semiconductive shielding layer was significantly reduced. The ability of the semiconducting shield to inhibit space charge injection from the conductive core to the insulation layer was significantly improved. When LiCoO2 content is 0.5 wt%, the semiconductive shielding layer has the best performance, and the space charge in the insulation layer was reduced by 70% compared to the undoped semiconducting shield.